Implementation of a Website-Based Proposal Seminar Registration System Using the Waterfall Method at Sheikh Abdul Halim Hasan Binjai Institute - Rizka, Rizka; Lubis, Fitra Hidayat; Berutu, Asro Hayati; Ritonga, Saprina Putri Utama; Gibran, M Khalil (Universitas Trilogi, 2025)
Registration of proposal seminars at the Sheikh Abdul Halim Hasan Binjai Institute is still done manually, which causes problems such as late information, errors in data recording, and lack of efficiency in administrative management. The institute currently has approximately 1,200 active students, with an average of 150–200 students submitting seminar proposals each semester. This increasing number of participants makes the manual system even more burdensome and prone to errors. To overcome these problems, a website-based proposal seminar registration system was implemented. This system is designed to make it easier for students to register, as well as help the administration in managing the data of seminar participants in a more effective and structured manner. The system development uses the PHP programming language with a MySQL database and the waterfall development method as a systematic approach in the implementation process. The results of the implementation show that the system is able to improve the efficiency of the registration process, minimize data errors, and provide real-time information for students and supervisors. With this system, it is expected that the proposal seminar administration process will become more organized and transparent.